STRATEGY FOR THE PROTECTION OF THE CIVILIAN POPULATION IN CONDITIONS OF FULL-SCALE WAR - Polukarov, Yury; Zemlyanska, Olena; Polukarov, Oleksiy; Prakhovnik, Nataliia; Kovtun, Andrii; Ignatiev, Oleksandr; Prisych, Kostiantyn (Collection of scientific papers «ΛΌГOΣ», 2024)
A full-scale war, which is facing the current world, will bring about unforeseen conflicts, which will endanger not only the territorial integrity, but also the safety of the population. The civilian population, which has become the most influential segment of marriage in the minds of the war, will require a comprehensive and well-thought-out defense [1].